The Influence of Leadership and Work Ethic on Employee Motivation at PT. Suryaindah Wiraperkasa Palembang - Rahmad Chandra Saputra; Siti Komariah Hildayanti; Shafiera Lazuarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyse the effect of leadership and work ethic on employee motivation at PT Suryaindah Wiraperkasa, Alang-Alang Lebar District, Palembang. The object of this research is all employees of PT Suryaindah Wiraperkasa, Alang-Alang Lebar District, Palembang as many as 40 people. The analysis technique used is multiple linear analysis which is processed using the help of the Statistical Product and Service Solution (SPSS) computer program version 26. Based on the results of data analysis obtained Leadership and Work Ethic have a positive and significant effect on Employee Work Motivation. Based on the results of data analysis, there is an influence of leadership and work ethic on employee motivation at PT Suryaindah Wiraperkasa, Alang-Alang Lebar District, Palembang.